2012
DOI: 10.1007/s10509-012-1331-z
|View full text |Cite
|
Sign up to set email alerts
|

On the metallicity dependence of classical Cepheid light amplitudes

Abstract: Classical Cepheids remain a cornerstone of the cosmic distance scale, and thus characterizing the dependence of their light amplitude on metallicity is important. Period-amplitude diagrams constructed for longer-period classical Cepheids in IC 1613, NGC 3109, SMC, NGC 6822, LMC, and the Milky Way imply that very metal-poor Cepheids typically exhibit smaller V -band amplitudes than their metal-rich counterparts. The results provide an alternate interpretation relative to arguments for a null and converse metall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…The former assertion is supported by observations indicating that longperiod Cepheids in NGC 6822 exhibit larger V-band amplitudes than metal-poor SMC Cepheids, and marginally smaller amplitudes than LMC Cepheids (Majaess et al 2013b). The trend agrees with certain models that produce 10 d −30 d metal-poor Cepheids which feature smaller amplitudes than their metal-rich counterparts (Bono et al 2000, for an alternate interpretation see Szabados & Klagyivik 2012).…”
Section: Ngc 6822supporting
confidence: 72%
See 2 more Smart Citations
“…The former assertion is supported by observations indicating that longperiod Cepheids in NGC 6822 exhibit larger V-band amplitudes than metal-poor SMC Cepheids, and marginally smaller amplitudes than LMC Cepheids (Majaess et al 2013b). The trend agrees with certain models that produce 10 d −30 d metal-poor Cepheids which feature smaller amplitudes than their metal-rich counterparts (Bono et al 2000, for an alternate interpretation see Szabados & Klagyivik 2012).…”
Section: Ngc 6822supporting
confidence: 72%
“…Cepheids in NGC 6822 could exhibit a mean abundance between SMC and LMC Cepheids (Venn et al 2001;Majaess et al 2013b, and references therein), and may thus bolster efforts to constrain the impact of metallicity on the distance scale. The former assertion is supported by observations indicating that longperiod Cepheids in NGC 6822 exhibit larger V-band amplitudes than metal-poor SMC Cepheids, and marginally smaller amplitudes than LMC Cepheids (Majaess et al 2013b).…”
Section: Ngc 6822mentioning
confidence: 93%
See 1 more Smart Citation
“…Such a clear relation between the light curve shape and the metallicity is not known for Cepheid stars. Although there are indications that metallicity affects the pulsation amplitudes of Cepheids, the nature of the dependence has been debated (Szabados & Klagyivik 2012;Majaess et al 2013). Recent efforts to estimate fundamental parameters such as mass, radius, luminosity, and effective temperature from photometry also demonstrated that light curve structure is statistically important both in RR Lyrae and Cepheid types (Bellinger et al 2020).…”
Section: Comparison With Modelsmentioning
confidence: 99%
“…The discrepancy is sufficient to hinder efforts to constrain the nature of dark energy (for which σ w ∼ 2σ H 0 , ), and could be linked to a systematic offset in the Cepheid calibration, or unreliable photometry for remote extragalactic Cepheids owing to crowding effects (Mochejska et al 2004;Majaess 2010Majaess , 2011a, see also Table 2 in Riess et al 2011). Research continues on the aforementioned topics irrespective of the discrepancy, namely to resolve the putative degeneracy between the impact of crowding and metallicity on Cepheid parameters (Majaess et al 2011a(Majaess et al , 2013aChavez et al 2012, and references therein), and to strengthen the Galactic Cepheid calibration (e.g., Majaess et al 2012a;Anderson et al 2013). That calibration is likewise important for defining the metallicity gradient of the Milky Way (Luck et al 2011), benchmarking standard candles (Matsunaga 2012;Kudritzki et al 2012), and constraining the behavior of intermediate mass stars (Neilson et al 2012;Bono et al 2013, and references therein).…”
Section: Introductionmentioning
confidence: 99%